Development of Community Craftsmen’s Skills in Construction Work to Alleviate Poverty in Ta Muang Sub-district, Ubon Ratchathani Province - Thanawattanawong, Chantha; Sanew, Sirisuda (Area Based Development Research Journal, 2023)
Ta Muang Sub-district, Ubon Ratchathani Province of Thailand is an area being prone to natural disasters. Community craftsmen in have the potential to build boats to evacuate people and property, and repair houses after flood situations However, these community craftsmen lack proper knowledge in accurate construction calculations, technical skills, and certification according to labor skill standards. Therefore, the objective of this research is to enhance human resources by developing vocational skills for community craftsmen and creating income opportunities through the following processes: Step 1: Participatory involvement of stakeholders in the area to identify and understand the root causes of problems; Step 2: Data collection on community craftsmen in Ta Muang Sub-district; Step 3; Designing a curriculum for developing vocational skills for community craftsmen in the area; Step 4: Implementation of community craftsmen’s skill development through training and practical work experience in real-life situations; Step 5: Evaluation of community craftsmen’s skill development in Ta Muang Sub-district, involving the participation of the Ubon Ratchathani Regional Skilled Labor Development Institute 7. In this step, the Institute conducts evaluations of the skill development program for community craftsmen in Ta Muang Sub-district. The institute provided training courses for 107 community craftsmen in the light brick wall course, product assembly welding course, and advanced solar for agriculture course. As a result of the training, 99 community craftsmen successfully obtained certified vocational skills in accordance with the respective training courses. Among the participants, 25 craftsmen specializing in lightweight brick wall construction experienced a 114.29% increase in income, and 10 craftsmen specializing in product assembly welding saw a 142.86% increase in income. Additionally, by applying solar cell systems in their households, 8 households managed to reduce their expenses by 400 Baht (about 11.40 US dollars) per month, while one household replaced fuel with solar cell systems, leading to a reduced monthly expense of 1,480 Baht (about 42.15 US dollars). Furthermore, the project also included activities for skilled community craftsmen, such as establishing a social network for construction craftsmen in Ta Muang Sub-district to provide assistance to households affected by disasters, benefiting 28 households. Additionally, houses were constructed for community members as part of the Baan Mankong Rural Project.